Shift in Kiss1 Cell Activity Requires Estrogen Receptor α - Frazão, Renata (Society for Neuroscience, 2013)
Reproductive function requires timely secretion of gonadotropin-releasing hormone, which is controlled by a complex excitatory/inhibitory network influenced by sex steroids. Kiss1 neurons are fundamental players in this network, but it is currently unclear whether different conditions of circulating sex steroids directly alter Kiss1 neuronal activity. Here, we show that Kiss1 neurons in the anteroventral periventricular and anterior periventricular nuclei (AVPV/PeN) of males and females exhibit a bimodal resting membrane potential (RMP) influenced by K(ATP) channels, suggesting the presence of two neuronal populations defined as type I (irregular firing patterns) and type II (quiescent). Kiss1 neurons in the arcuate nucleus (Arc) are also composed of firing and quiescent cells, but unlike AVPV/PeN neurons, the range of RMPs did not follow a bimodal distribution. Moreover, Kiss1 neuronal activity in the AVPV/PeN, but not in the Arc, is sexually dimorphic. In females, estradiol shifts the firing pattern of AVPV/PeN Kiss1 neurons and alters cell capacitance and spontaneous IPSCs amplitude of AVPV/PeN and Arc Kiss1 populations in an opposite manner. Notably, mice with selective deletion of estrogen receptor α (ERα) from Kiss1 neurons show cellular activity similar to that observed in ovariectomized females, suggesting that estradiol-induced changes in Kiss1 cellular properties require ERα. We also show that female prepubertal Kiss1 neurons are under higher inhibitory influence and all recorded AVPV/PeN Kiss1 neurons were spontaneously active. Collectively, our findings indicate that changes in cellular activity may underlie Kiss1 action in pubertal initiation and female reproduction.